VIGOLT system for solving transport logistics optimization problems - Bukharov, D.S.; Bukharov, D.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
VIGOLT system is described. The system is used to solve a number of logistic problems given in continuous formulation: the optimal path problem, the problem of optimal location for logistic objects and the segmentation problem of logistic areas. Numerical algorithms based on optical-geometrical analogy are implemented. A parallel algorithm for solving the optimal location problem for several logistic objects is proposed. The algorithms are tested on various multiprocessor computers. This work was supported by the Russian Foundation for Basic Research (project N 11-07-00245).